Web Optimization of Compression Ignition Aviation Engine Crankshaft - Serkan Galata; Yiğit Okur; Ülkü Uzan; Emre Ünlü; Kudret Muhziroğlu; Övün Işın; Mehmet Oğuz Turgut; Emin Tuzlu (International Journal of Aerospace Engineering)
The focus of this study was the weight reduction of crankshaft web regions of an inline 4 cylinder, 250 HP compression ignition engine with a combustion chamber volume of 2499 cm3 intended for use in aircraft. Iteration #0 model was generated by manual reduction of a reference model. According to the results of the analyses, the stresses were compared. Since the increase in stress values of weight reduced model over the reference model exceeded the targeted upper limit of 15.0%, three geometric parameters have been defined, and seven candidate design models have been created by using one, two, or all of the three parameters. In order to maximize the weight reduction by achieving the target stress limit, the lightest design model was obtained in the 10th iteration. For the last three iterations, new parametric values were determined by utilizing the calculated effects of the geometric parameters on stress and weight.